Assessing the vulnerability of Indian mustard to climate change - Boomiraj K; Chakrabarti, B.; Aggarwal, Pramod K.; Choudhary R; Chander, S. (Elsevier, 2010)
Rapeseed-mustard (Brassica spp.) is a major group of oilseed crop in the world with India being the second largest cultivator after China. Although there has been a significant increase in oilseed production since 1960s, the demand for oilseeds production in the future is likely to go up due to population increase and their income. Mustard is much sensitive to climatic variables and hence climate could have significant effect on its production. There are very limited studies to assess the impact of climate change on oilseed crops as compared to cereals. This paper presents results of a simulation study to evaluate the impact of projected climate change on Indian mustard (Brassica juncea) in contrasting agro-environments of the tropics. InfoCrop, a generic dynamic crop model, provides integrated assessment of the effect of weather, variety, pests and soil management practices on crop growth and yield, as well as on soil nitrogen and organic carbon dynamics in aerobic, anaerobic conditions and also greenhouse gas emissions. The validated model (InfoCrop-mustard) has reasonably predicted phenology, crop growth and yield of mustard crop. The crop was found to be sensitive to changes in carbon dioxide (CO2) and temperature. Future climate change scenario analysis showed that mustard yields are likely to reduce in both irrigated and rainfed conditions. However, these reductions have spatial variation in different mustard growing region of India. In both irrigated and rainfed conditions, yield reduction would be higher in eastern India (67 and 57%) followed by central India (48 and 14%) and northern India (40.3 and 21.4%). This was due to maximum temperature rise in eastern part of the country, projected for 2080. In northern India, yield reduction of irrigated mustard was comparatively less due to prevailing lower temperature in this region during the crop growth period. But rainfed crop was found to be more susceptible to changing climate in north India due to projected reduction in rainfall in future scenarios. Adoption of adaptation measures like late sowing and growing long-duration varieties would be helpful in preventing yield loss of irrigated mustard in different locations of the country.